Ethiopia Alive & Thrive Baseline Survey 2010: Supervisors of Health Extension Workers - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the supervisors of health extension workers survey that was conducted to gather data at baseline as a part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions, delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of IYCF practices in two regions where the IFHP operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The Ethiopia baseline survey had two broad objectives. The first objective was to gather data on the primary impact indicators of the evaluation, prior to implementation of any A&T interventions, to establish a baseline against which changes would be measured. The second objective was to assess different factors that may influence the outcomes of interest, and thus shape the impact of the primary impact indicators. These factors were determined at five different levels: 1) child, 2) maternal/caregiver, 3) household, 4) community, 5) health care providers, 6) health system. These factors will also provide useful information to interpret the results of the impact evaluation and also signal key issues to pay attention to in the process evaluation. The Ethiopia baseline survey used five separate questionnaires that aimed to capture elements along the program impact pathways. These tools include 1) a household questionnaire, 2) a staff questionnaire of HEWs, 3) a staff questionnaire of supervisors of HEWs, 4) a VCHP), and 5) a community questionnaire. Three types of health staff questionnaires (HEW, VCHP, and supervisors) applied to health staff who are closest to the community or work in the community. These questionnaires were aimed at assessing three major issues: 1) frequency of interactions between health staff and caregivers, and avenues for these interactions; 2) content of the discussion between caregivers and health staff, and the time spent on IYCF-related discussions; and 3) knowledge and training received by the health staff on IYCF. The roles of the supervisors are somewhat different from the other two types of health staff. They do not come in direct contact with caregivers, yet they are mainly responsible for providing training to the HEWs and monitoring and supervising the training of volunteers, conducted by the HEWs. The questionnaire for supervisors, therefore, aims at capturing these interactions. Together, combining information from the HEW/VCHP questionnaires with those administered to the supervisors of individual staff in the survey will generate valuable data on the organization context for the FHWs prior to the introduction of A&T interventions in the health system.